Eliciting unnatural immune responses by activating cryptic epitopes in viral antigens. Issue 9 (23rd March 2018) - Lee, Young Jae; Yu, Ji Eun; Kim, Paul; Lee, Jeong-Yoon; Cheong, Yu Cheol; Lee, Yoon Jae; Chang, Jun; Seong, Baik Lin
ABSTRACT: Antigenic variation in viral surface antigens is a strategy for escaping the host's adaptive immunity, whereas regions with pivotal functions for infection are less subject to antigenic variability. We hypothesized that genetically invariable and immunologically dormant regions of a viral surface antigen could be exposed to the host immune system and activated by rendering them susceptible to antigen‐processing machinery in professional antigen‐presenting cells (APCs). Considering the frequent antigen drift and shift in influenza viruses, we identified and used structural modeling to evaluate the conserved regions on the influenza hemagglutinin (HA) surface as potential epitopes. Mutant viruses containing the cleavage motifs of cathepsin S within HA were generated. Immunization of mice showed that the mutant, but not the wild‐type virus, elicited specific antibodies against the cryptic epitope. Those antibodies were purified, and specific binding to HA was confirmed. These results suggest that an unnatural immune response can be elicited through the processing of target antigens in APCs, followed by presentation via the major histocompatibility complex, if not subjected to regulatory pathways. By harnessing the antigen‐processing machinery, our study shows a proof‐of‐principle for designer vaccines with increased efficacy and safety by either activating cryptic, or inactivating naturally occurring, epitopes of viral antigens.—Lee, Y. J., Yu, J. E., Kim, P., Lee, J.‐Y., Cheong, Y. C., Lee, Y. J., Chang, J., Seong, B. L. Eliciting unnatural immune responses by activating cryptic epitopes in viral antigens. FASEB J. 32, 4658–4669 (2018). www.fasebj.org